NFC/센서를 이용한 실시간 시약 관리 시스템 - 김호성(Ho-Sung Kim); 장재명(Jae-Myung Jang); 정회경(Hoe-Kyung Jung) (한국정보통신학회논문지, 2016)
Recent developments in internet technologies has enabled widespread growth of embedded systems like Arduino, Raspberry Pi and other smart home systems. A research in the industrial sector on the utilization of the board has been made. The development needs of the embedded board in a reagent bottle case system has been highlighted. Current reagent Management System has to hold and manage the reagent itself is mostly to save the program using handwritten or machine. In addition, there is a risk to the system during the vulnerable zone administrator to manage the situation of the reagent bottle case can lead to a massive fire. In this paper, reagent bottle case RFID readers and data in real-time is monitored by attaching a sensor management through the database and sends a warning message to the mobile device of the administrator in real time during hazardous situations in the reagent bottle case. This is improve the reliability and efficiency of reagent bottle case. 최근 Arduino, Raspberry Pi 등 임베디드(Embedded) 보드의 보편화와 인터넷 기술 발달로 인해 스마트 홈 및 산업분야에서 이를 활용한 연구가 이루어지고 있다. 그 중에서도 시약장과 임베디드 보드가 융합된 스마트 시약장의 개발 필요성이 부각되고 있다. 현재 시약 관리 시스템은 시약 자체를 보관하거나 관리하는데 있어 수기 또는 컴퓨터를 사용하여 프로그램에 저장하는 것이 대부분이다. 또한 사용자가 시약장을 관리하기에 취약한 시간대에 위험 상황 발생 시 관리자가 인식하지 못할 경우 큰 화재가 발생할 수 있다. 본 논문에서는 시약장에 RFID리더기 및 센서를 부착한 뒤 입력받은 데이터를 데이터베이스에서 관리 하여 사용자에게 보여주고, 시약장 내부에서 이상 상황 시 실시간으로 모바일 기기에 경고 메시지를 전송하여 취약 시간에도 위험 상황을 알려주는 시스템을 설계 및 구현한다. 이는 시약장의 안정성과 효율성을 향상 시킬 수 있을 것으로 판단된다.